Effects of Gestational and Lactational Fenvalerate Exposure on Immune and Reproductive Systems of Male Rats - Nassr, Azize C. C.; Arena, Arielle C.; Toledo, Fabiola C.; Bissacot, Denise Z. [UNESP]; Fernandez, Carla; Spinardi-Barbisan, Ana Lucia T. [UNESP]; Pires, Paulo W. [UNESP]; Kempinas, Wilma (Taylor & Francis Inc, 2010)
The aim of this study was to determine the consequent reproductive developmental and immunotoxic effects due to exposure to fenvalerate during pregnancy and lactation in male offspring of maternal-treated rats. Pregnant rats were treated daily by oral gavage with 40 or 80 mg/kg of fenvalerate or corn oil (vehicle, control), from d 12 of pregnancy to d 21 of lactation. Immune and reproductive developmental effects were assessed in male offspring at postnatal days (PND) 40 (peripuberty), 60 (postpuberty), and 90 (sexual maturity). Treatment with the higher dose (80 mg/kg) resulted in convulsive behavior, hyperexcitability, and mortality in 45% of the dams. Fenvalerate was detected in the fetus due to placental transfer, as well as in pups due to breast-milk ingestion, persisting in male offspring until PND 40 even though pesticide treatment was terminated on PND 20. However, fenvalerate did not produce marked alterations in age of testicular descent to the scrotum and prepucial separation, parameters indicative of puberty initiation. In contrast, at puberty, there was a reduction in testicular weight and sperm production in male offspring of maternal-treated rats. At adulthood, the sperm counts and fertility did not differ between control and treated groups. Testosterone levels were not changed at any time during reproductive development. Similarly, no apparent exposure-related effects were detected in the histological structures of the lymphohematopoietic system. Data indicate that fenvalerate, in this experimental model, interfered with initial development of the male reproductive system, but that these effects on sperm production or fertility did not persist into adulthood. There was no apparent evidence that fenvalerate altered testosterone levels or produced a disruption in male endocrine functions.